2004
DOI: 10.1093/ps/83.1.15
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Bird Age, Density, and Molt on Behavioral Profiles of Two Commercial Layer Strains in Cages

Abstract: Two commercial strains, Hy-Line W-36 and DeKalb XL, were moved to a laying house at 18 wk of age. They were housed 6 hens/layer cage at 2 densities (361 and 482 cm2/bird) with 2 replications each per strain/density combination. The high-density treatment contained 24 hens/replication and the low-density treatment contained 18 hens/replication for a total of 168 hens. Production parameters were measured during the first egg production cycle, the molt period, and the first 4 wk of the second lay cycle (20 to 68 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
17
0
1

Year Published

2005
2005
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(30 citation statements)
references
References 25 publications
5
17
0
1
Order By: Relevance
“…The time used by these hens in each respective posture and behavior is in agreement with previous laying hen behavioral research (Webster, 2000;Anderson et al, 2004). Therefore, any differences reported in the subsequent molt and postmolt periods could be attributed to the low-energy molt diets.…”
Section: Baseline Periodsupporting
confidence: 89%
See 1 more Smart Citation
“…The time used by these hens in each respective posture and behavior is in agreement with previous laying hen behavioral research (Webster, 2000;Anderson et al, 2004). Therefore, any differences reported in the subsequent molt and postmolt periods could be attributed to the low-energy molt diets.…”
Section: Baseline Periodsupporting
confidence: 89%
“…Webster (2000) and Biggs et al (2004;housed 3 hens/cage at 460 cm 2 /hen) reported no differences in aggressive pecking behaviors when comparing WM and FW molt treatments, but McCowan et al (2006) noted that cage pecking increased in hens (housed 3 hens/cage at 417 cm 2 /hen) assigned to an FW molt, and aggression increased in hens assigned to an FW and a non-FW molt during the molt period. Webster (2000), Anderson et al (2004), and Biggs et al (2004) reported in agreement across studies that FW birds did not show an increase in aggression, nonnutritive pecking, or sitting when compared with birds that still had access to a low-energy feed during molt. The 2 d of observations during molt were averaged before the final analysis because no difference was observed between observation days for each behavioral trait.…”
Section: Low-energy Molt Diets Pre-and Postmoltsupporting
confidence: 74%
“…Decreasing egg production was shown to be attributable to the reduced feeding area per hen, cannibalism (Hester and Wilson, 1986;Craig and Milliken, 1989;Lee and Moss, 1995;Süto et al, 1997;Sohail et al, 2001;Onbasilar and Aksoy, 2005;Jalal et al, 2006;Nicol et al, 2006) and stocking density (Adams and Craig, 1985). Anderson et al (2004) found out that the reduced cage stocking in Hy-Line W36 and Dekalb XL commercial layer genotypes decreased hen-day egg production. They reported a decrease in egg production from 82.3% to 77.4% because of reducing the cage stocking from 482 cm 2 to 361 cm 2 per hen.…”
Section: Discussionmentioning
confidence: 99%
“…A decrease in floor densities causes a reduction in egg production (EP), egg weight (EW) and feed intake (FI), an increase in mortality and feather pecking with poorer plumage scores (Bell, 1981;Roush et al, 1984;Anderson et al, 1989;Sandoval et al, 1991;Hester et al, 1996;Huber-Eicher and Sebö, 2001;Anderson et al, 2004;Onbasilar and Aksoy, 2005;Tauson, 2005;Jalal et al, 2006;Nahashon et al, 2006;Nicol et al, 2006). However, there is still a need to carry out further studies regarding egg production, egg quality, lower mortality and plumage damage of layers, as responses to reduced cage densities.…”
mentioning
confidence: 99%
“…, 1970;GROVER et al, 1972;CONNOR E BURTON 1975;CUNNINGHAM E OSTRANDER, 1981;CUNNINGHAM, 1982;CUNNINGHAM E OSTRANDER, 1982;ROUSH et al, 1984;CUNNINGHAM E GVARYAHU, 1987;CUNNINGHAM et al, 1987;CUNNINGHAM et al, 1988;ANDERSON et al, 2004;ON AŞILA E AKSOY, 2005;NAHASHON et al, 2006;DE MORAES GARCIA et al, 2015).…”
Section: Produção De Ovosmentioning
confidence: 99%